Dividend Policy and New Equity Financing: Discussion - Brigham, E. F. (Journal of Finance, 1971)
E. F. Brigham, Dividend Policy and New Equity Financing: Discussion, The Journal of Finance, Vol. 26, No. 2, Papers and Proceedings of the Twenty-Ninth Annual Meeting of the American Finance Association Detroit, Michigan December 28-30, 1970 (May, 1971), pp. 540-542